Revisiting the Old Data of Heat Shock Protein 27 Expression in Squamous Cell Carcinoma: Enigmatic HSP27, More Than Heat Shock - Shutao Zheng; Yan Liang; Lu Li; Yiyi Tan; Qing Liu; Tao Liu; Xiaomei Lu (Cells, 2022)
Initially discovered to be induced by heat shock, heat shock protein 27 (HSP27, also called HSPB1), a member of the small HSP family, can help cells better withstand or avoid heat shock damage. After years of studies, HSP27 was gradually found to be extensively engaged in various physiological or pathophysiological activities. Herein, revisiting the previously published data concerning HSP27, we conducted a critical review of the literature regarding its role in squamous cell carcinoma (SCC) from the perspective of clinicopathological and prognostic significance, excluding studies conducted on adenocarcinoma, which is very different from SCC, to understand the enigmatic role of HSP27 in the tumorigenesis of SCC, including normal mucosa, dysplasia, intraepithelial neoplasm, carcinoma in situ and invasive SCC.